123k views
5 votes
How do I solve problem (B) on the attached problem?

How do I solve problem (B) on the attached problem?-example-1

1 Answer

5 votes

Solution

Given:

(a)


\begin{gathered} f(x)=x+2 \\ g(x)=x-2 \\ \end{gathered}

(1)


\begin{gathered} f\mleft(g\mleft(x\mright)\mright)=(x-2)+2 \\ f\mleft(g\mleft(x\mright)\mright)=x-2+2 \\ f\mleft(g\mleft(x\mright)\mright)=x \end{gathered}

(2) =


\begin{gathered} g\mleft(f\mleft(x\mright)\mright)=(x+2)-2 \\ g(f(x))=x+2-2 \\ g(f(x))=x \end{gathered}

(3)


\begin{gathered} For\text{ the two functions to be inverse of each other , then the condition below must be satisfied} \\ f(g(x)\text{ = g\lparen f\lparen x\rparen\rparen = x} \end{gathered}

Thus, f and g are inverses of each other.

User Bishwarup Das
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.